1985
DOI: 10.1073/pnas.82.2.259
|View full text |Cite
|
Sign up to set email alerts
|

The primary process of vision and the structure of bathorhodopsin: a mechanism for photoisomerization of polyenes.

Abstract: A model for the primary process of vision is proposed, which involves a novel concerted-twist motion. Application of such motions to rhodopsin and bathorhodopsin successfully accounts for the properties of bathorhodopsin and related intermediates, including specific assignment of molecular structures to bathorhodopsin, to lumirhodopsin, and, less specifically, to hypsorhodopsin.In this paper we propose a mechanism for cis-trans isomerization of polyenes. This mechanism is a special case applicable only to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
169
0

Year Published

1988
1988
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(173 citation statements)
references
References 36 publications
4
169
0
Order By: Relevance
“…This step initiates the isomerization and is characterized by a concerted double bicycle-pedal mechanism (40) (illustrated in Fig. 4B) with a minor contribution of hula twist (52) involving tiny pyramidalizations at C12 and C13 [this pyramidalization was also reported by Hayashi et al (31), but at a different location, C14, perhaps due to reduced QM moiety employed in the simulations]. As shown in Fig.…”
Section: Photoisomerization Photoproduct Formation and Retinal Dipolementioning
confidence: 84%
“…This step initiates the isomerization and is characterized by a concerted double bicycle-pedal mechanism (40) (illustrated in Fig. 4B) with a minor contribution of hula twist (52) involving tiny pyramidalizations at C12 and C13 [this pyramidalization was also reported by Hayashi et al (31), but at a different location, C14, perhaps due to reduced QM moiety employed in the simulations]. As shown in Fig.…”
Section: Photoisomerization Photoproduct Formation and Retinal Dipolementioning
confidence: 84%
“…Previous models, such as the bicycle-pedal model 36 and the hula-twist model, 37 suggested that, upon photoisomerization, rotation around the C11 = C12 bond propagated to neighboring double and/or single bonds. Our model for Batho shows that, besides the C11 = C12 bond, the C7 = C8 double bond undergoes a large rotation in a bicycle-pedal fashion; in addition, every bond between these double bonds also twists to form a curved structure.…”
Section: Discussionmentioning
confidence: 99%
“…Liu et al [194] proposed a model for the primary process of vision involving a concertedtwist motion. Hayward et al [195] suggested that the isomerisation is complete within picoseconds after the absorption of a photon.…”
Section: Retinamentioning
confidence: 99%